Penghasilan Karya Sintesis Antara Mantik dan Usul al-Fiqh: Rujukan kepada Kitab al-Mustasfa min ’Ilm al-Usul, Karangan al-Imam al-Ghazzali (M. 505h. / 1111M.) - Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
This article tries to expound the contribution of al-Ghazzali through his popular work in Islamic Jurisprudence namely al-Mustasfa min ’Ilm al-Usul. The discussion will focus on its important criteria of combination or synthesis between Usul al-Fiqh as a discipline based on al-Shafi’i’s Methodology and Logic based on Aristotelian Logic. The act of al-Ghazzali in performing logic as a brief introduction (muqaddimah) for this book will be highlighted in this article.